Influencia ambiental sobre los hábitos alimentarios del lobo marino de un pelo sudamericano Otaria flavescens en Promontorio Belén (Río Negro-Argentina) - Harrington, Ana (2025)
Marine mammals are at the highest levels of the trophic webs, so the study of their feeding ecology allows us to interpret their role in the trophic structures of marine ecosystems. Sea lions can be good indicators of spatial and temporal changes in the distribution and abundance of the marine resources they prey upon. Furthermore, the availability of food in the ocean is one of the most influential factors in the population fluctuations of otariids. Consequently, understanding the predator-prey relationship is an important tool for achieving proper management in the conservation of species, as well as the fisheries operating in the area, given the potential overlap with humans in the use of marine resources.\nClimatological and oceanographic events, whose scope of influence extends beyond their generation zone to distant regions across different latitudes, entail changes in the marine ecosystem. The influence of these events causes changes in the availability of certain prey species for sea lions. Therefore, integrating biological and oceanographic data has the potential to provide a better understanding of ecosystem dynamics.\nThe aim of this thesis was to evaluate the trophic habits and feeding strategies of the South American sea lion (Otaria flavescens) (Carnivora, Otariidae) and the potential environmental influence on its trophodynamics, in order to interpret its role as an apex predator in the northern Patagonian marine ecosystem.\nA total of 513 scat samples from O. flavescens were collected over 7 summers (2012-2018) and 3 springs (2011, 2012 and 2017) at the Promontorio Belén colony (41° 09'S; 63° 48'O), province of Río Negro. The samples were preserved in 70% ethanol and analyzed in the laboratories of the Instituto de Investigaciones en Producción Animal (INPA/UBA-CONICET) and the Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACNBR-CONICET). Additionally, blood and whiskers samples were collected and analyzed using stable isotope techniques. After sieving the scat samples, hard remains were classified to the lowest possible taxonomic level using identification guides. The frequency of occurrence (%FO), numerical abundance (%N), biomass (%M) and relative importance index (%IRI) of the main prey ítems were determined.\nThe analysis determined that O. flavescens mainly consumed fish (%FO 96,6%), cephalopods (%FO 77,2%) and crustaceans (%FO 40,7%), focusing its foraging activity in predominantly benthic and demersal-benthic environments associated with coastal waters and the Argentine Continental Shelf. Significant interannual differences were found in the occurrence of these three prey taxa during spring sampling, but not in summer.\nBased on the identification of 5406 sagitta otoliths, the presence of 24 species of bony fish from 18 families was determined. The banded cusk eel (Raneya brasiliensis) (Ophidiidae) was the dominant prey species in all sampling seasons, followed by the toadfish (Porichthys porosissimus) and the rockfish (Triathalassothia argentina). Isolation of 2089 cephalopod beaks revealed that octopods had a higher frequency of occurrence than teuthids (44,5% vs. 35,2%). The former was mostly represented by the Tehuelche octopus (Octopus tehuelchus), while the latter were represented by the Patagonian longfin squid (Doryteuthis gahi). Starting in the summer of 2015, a marked increase in the predation of Argentine red shrimp (Pleoticus muelleri) was observed, coinciding with the rise in fishery catches, suggesting a population increase and greater availability of this crustacean.\nThe isotopic values obtained reflect a diet based on species of relatively low trophic level, consumed in coastal and benthic environments, validating the findings observed through the scat analysis.\nThe main species preyed upon by sea lions are not of commercial interest. Commercially valuable species, such as the common hake and the Argentine squid, are minor prey items in their diet. This indicates minimal to no overlap in the use of resources. In contrast, in the San Matías Gulf, the artisanal fishery for the Tehuelche octopus could compete with sea lions. Therefore, monitoring both, commercial (mainly shrimp) and artisanal fisheries, is essential to ensure adequate management of these activities, without compromising the populations of target species or the predators that interact with them both operationally and ecologically.\nDietary variations in the sea lion were found starting in the summer of 2016, which may possibly be a consequence of the environmental changes recorded in the Southwest Atlantic Ocean. These changes could be associated with the 2015/16 "El Niño" phenomenon, which turned out to be one of the strongest events recorded to date.\nThe application of otolith morphometry analysis found in the scats of sea lions allows for the assignment, within the existing stocks, of which one is consumed by this otariid. In the studied case of Porichthys porosissimus, it was determined that the population preyed upon the sea lions of Promontorio Belén belongs to the same stock as the populations of this species in southern Buenos Aires.\nThis study provides, for the first time, information on the feeding ecology and trophodynamics of the O. flavescens population from Promontorio Belén (Río Negro). The variations in the diet due to changes recorded in oceanographic variables, confirm the generalist and opportunistic foraging behavior, positioning it as a key apex predator in the San Matías Gulf, as well as an indicator species of the state of the marine ecosystem. Additionally, it is essential to consider the South American sea lion as a natural biological sampler of R. brasiliensis, which is a key species in the food webs of the northern Patagonian marine ecosystem.\nThe results provide baseline information for the implementation of public policies by the Secretaría de Ambiente y Cambio Climático of Río Negro, in order to establish, for the first time, management and conservation measures for this colony.